2014
DOI: 10.1007/s11010-013-1929-7
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in glutathione S-transferase are risk factors for perioperative acute myocardial infarction after cardiac surgery: a preliminary study

Abstract: In the present study we explored glutathione S-transferase (GST) polymorphisms in selected patients who experienced accelerated myocardial injury following open heart surgery and compared these to a control group of patients without postoperative complications. 758 Patients were enrolled from which 132 patients were selected to genotype analysis according to exclusion criteria. Patients were divided into the following groups: Group I: control patients (n = 78) without and Group II.: study patients (n = 54) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The recognition that GST genes are consistently altered in various animal models of lung injury and are among the top genes that accurately predict development of primary graft failure in lung transplant donors (19) certainly points toward these promising directions. Our pilot genetic data may also highlight a role of specific GST gene polymorphism in the development of perioperative myocardial infarction (20), thus extending the paradigm beyond lung ischemia reperfusion injury.…”
Section: Discussionmentioning
confidence: 87%
“…The recognition that GST genes are consistently altered in various animal models of lung injury and are among the top genes that accurately predict development of primary graft failure in lung transplant donors (19) certainly points toward these promising directions. Our pilot genetic data may also highlight a role of specific GST gene polymorphism in the development of perioperative myocardial infarction (20), thus extending the paradigm beyond lung ischemia reperfusion injury.…”
Section: Discussionmentioning
confidence: 87%
“…Glutathione S-transferase (GST) polymorphism is identified as one of the factors that could lead to an increased incidence of MI during cardiac surgery. To investigate the association between GST polymorphism and MI, Kovacs et al [121] conducted a study on 758 patients that had cardiac surgery. After measuring levels of troponin 1 (T1) and myocardial-based creatine kinase (CKMB), two groups of patients were formed.…”
Section: Glutathione In Cvsmentioning
confidence: 99%
“…On the other hand, allele AC was detected in a group of patients with MI. Authors suggested that the presence of allele B may have a protective role in the development of MI, while the presence of alleles A and C was associated with increased risk for MI [121].…”
Section: Glutathione In Cvsmentioning
confidence: 99%
“…The authors concluded that the reduction of glutathione levels in plasma may be an independent risk factor for the development of cardiovascular disease. Kovacs et al . investigated the link between myocardial infarction and glutathione S‐transferase polymorphism in patients that underwent cardiac surgery using genetic tests.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the reduction of glutathione levels in plasma may be an independent risk factor for the development of cardiovascular disease. Kovacs et al 35 investigated the link between myocardial infarction and glutathione S-transferase polymorphism in patients that underwent cardiac surgery using genetic tests. The results suggested that the presence of allele B might have a potential role for protecting in the development of myocardial infarction, while the presence of alleles A and C could be associated with an increased risk of myocardial infarction.…”
Section: Glutathione Metabolism As a Potential Target For Therapy In mentioning
confidence: 99%